2019
DOI: 10.1002/ppul.24335
|View full text |Cite
|
Sign up to set email alerts
|

Pressure support ventilation, sigh adjunct to pressure support ventilation, and neurally adjusted ventilatory assist in infants after cardiac surgery: A physiologic crossover randomized study

Abstract: Objectives: We sought to compare gas exchange, respiratory mechanics, and asynchronies during pressure support ventilation (PSV), sigh adjunct to PSV (PSV SIGH), and neurally adjusted ventilatory assist (NAVA) in hypoxemic infants after cardiac surgery.Design: Prospective, single-center, crossover, randomized physiologic study.Setting: Tertiary-care pediatric intensive care unit.Patients: Fourteen hypoxemic infants (median age 11.5 days [8.7-74]). Interventions:The protocol begins with a 1 hour step of PSV, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In the abovementioned study [39], as in other studies [14,40], NAVA determined a significant reduction of peak inspiratory airway pressure and mean airway pressure when compared to conventional ventilation modes. In our study, peak inspiratory airway pressure was similar in all tested conditions, as we set the NAVA level to achieve similar peak inspiratory pressures to those observed during PSV.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the abovementioned study [39], as in other studies [14,40], NAVA determined a significant reduction of peak inspiratory airway pressure and mean airway pressure when compared to conventional ventilation modes. In our study, peak inspiratory airway pressure was similar in all tested conditions, as we set the NAVA level to achieve similar peak inspiratory pressures to those observed during PSV.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies confirmed the clinical feasibility and advantages of NAVA in pediatric patients after cardiac surgery [38,39] especially in patients with difficult weaning.…”
Section: Discussionmentioning
confidence: 82%
“…These results are consistent with our previous study in children with single ventricles [ 14 ] and many other studies [ 12 , 15 , 16 , 17 ]. In some studies of the NAVA mode, children ventilated with the NAVA mode had lower airway pressures than children ventilated with the continuous positive airway pressure mode, suggesting that the NAVA mode used before weaning may be more appropriate than the other modes [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that the incidence rate of the asynchronous index (AI) in the PSV mode was 36%, which was significantly higher than that in the NAVA mode. These problems will reduce the comfort of mechanical ventilation and increase dependence on sedatives (Bonacina et al., 2019 ). The results showed that the asynchronous index of Nava model was significantly lower than that of CPAP mode.…”
Section: Discussionmentioning
confidence: 99%